Distribución espacial de escarabajos coprófagos en áreas distantes a la carretera Iquitos-Nauta, Km. 26.5, Loreto-Perú - Amaya Tayme, Miguel Angel (2024)
From December 2023 to March 2024, dung beetles were captured in areas distant from the Iquitos-Nauta highway, Km. 26.5. The purpose of the research work was to evaluate the spatial distribution of dung beetles. Four transects were established 500 meters apart; pitfall traps with an attractive bait were used to capture them. 38 species distributed in 12 genera were collected. The transect at 500 meters was the one that presented the highest richness with 30 species and the transect at 0 meters with the lowest richness with 18 species. The transect at 1000 meters was the most abundant with 1033 individuals, the transect at 0 meters was the least abundant with 164 individuals. The species Canthon aequinoctiales was the most abundant in all transects. Dichotomius batesi is the only species captured on the edge and another 6 species have a very low frequency of occurrence. When carrying out the relationship of the distance between richness, abundance and occurrence, there is no strong relationship, whose variability would be influenced by other variables.